IMPLIKASI KRISIS EKONOMI TERHADAP DESA IDT DAN DESA BUKAN IDT: STUDI KOMPARATIF DESA PURWOHARJO DAN DESA GERBOSARI, KECAMATAN SAMIGALUH, KABUPATEN KULONPROGO, DIY - Sulistyaningrum, Eny; Adela, Elphiwin (Journal of Indonesian Economy and Business, 2001)
Indonesian economic crisis, emerged since 1997, has been an agony carrier for the entire Indonesian economy. Was that statement correct? A field trip to rural areas of an Indonesian Economy Class at the Faculty of Economics Gadjah Mada University, carried out on 25 October 2000, intended to further discover the truth or the flaw of the statement. The study trip was a direct observation of the life and interview of the people in Purwoharjo and Gerbosari. Major concern was the impact of the monetary crisis, known as âkrismonâ, to Poor and Non Poor villagers. The filled questionaires analysed by crosstabulation method is presented below. Six hypotheses analyzed. The dependent variable is the impact of the monetary crisis experienced by the respondents. The acceptance of most of the null hypotheses suggests that there is no implication of various independent variables such as income groupings and poverty line to dependent variable, that is the impact of the monetary crisis to the life of the rural population.Keywords: poor and non poor villages, social safety net, poverty, income groupings.